Traditional Know-How for Earthquake Resistance: The Logical Framework of Coffered Wall and Ceiling Systems in Historical Antakya Houses - Rifaioglu, Mert Nezih; Hurol, Yonca; Sahali, Oeznem (Taylor & Francis Inc, 2025)
Antakya, which is located in Southeast Turkiye, has unique traditional houses with coffered masonry stone walls with timber rectangular prisms and multileveled dome-like ceilings, called tekne tavan in local terminology, which perform relatively satisfactorily during earthquakes. There is a high earthquake risk in Antakya, and during the February 2023 earthquakes these traditional houses were affected. These structures are lighter than other masonry structures because they combine stone walls, timber elements, and coffers in their walls and ceilings. The objective of this article is to understand the logic behind these tectonic structures that do not have a place in literature. The article presents the structures of Antakya houses based on a systematic on-site investigation before and after the recent earthquakes as well as a systematic analysis of a building by 3D digital laser scanner documenting, enabling precise understanding of its process of construction. It can also be useful for restoration/rebuilding of damaged historic Antakya houses by providing historical know-how for earthquake resistance.
Keywords: Antakya houses; coffered ceilings; coffered walls; earthquake resistance; masonry structures; stone masonry